2005
DOI: 10.4028/www.scientific.net/msf.488-489.427
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure and Processing in Twin Roll Casting of Magnesium Alloy Strip

Abstract: Magnesium has a hexagonal close-packed crystal structure which makes it more difficult to deform than aluminum. Conventional strip production usually requires several process steps to reach the final strip thickness. Strip casting can reduce some of the process steps and make strip processing simpler and easier, especially for alloys with poor deformability. The twin-roll casting process can directly obtain strips with thickness less than one or two millimeters. In this paper, the metallurgical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…35 However, in the alloys exhibiting wider freezing ranges than AZ31 alloy, such as AZ61 (∆T o =85 K), AZ91 (∆T o =130 K), and several Mg-Zn based alloys (∆T o 115 K) that have larger alloying content than AZ31 alloy, a fully equiaxed dendritic structure was observed through the thickness of the as-cast strip. [14][15][16]23,26,[58][59][60] Another important characteristic of the Mg sheet fabricated by TRC is the less pronounced basal texture than the one by ingot casting.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, in the alloys exhibiting wider freezing ranges than AZ31 alloy, such as AZ61 (∆T o =85 K), AZ91 (∆T o =130 K), and several Mg-Zn based alloys (∆T o 115 K) that have larger alloying content than AZ31 alloy, a fully equiaxed dendritic structure was observed through the thickness of the as-cast strip. [14][15][16]23,26,[58][59][60] Another important characteristic of the Mg sheet fabricated by TRC is the less pronounced basal texture than the one by ingot casting.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…On the other hand, fabrication of Mg alloy strips by vertical TRC has also been reported. [35][36][37] Ding et al conducted a comparative study between vertical and horizontal TRC for Mg alloys. They concluded that horizontal TRC is suitable for producing wide sheets and thus favorable for commercialization due to the relatively easy control of uniform melt distribution while vertical TRC is advantageous with fast casting speed.…”
Section: Magnesium Alloy Twin Roll Castingmentioning
confidence: 99%
“…However, the cost can be reduced via near-net shape casting processes such as thin slab casting, single-belt casting and twin-roll casting (TRC) [8]. The TRC produces the thinnest as-cast sheet (with thickness less than 6 mm) [9] and is the most economical process, with investment costs that are 1/3 to 1/4 of the conventional Mg sheet production process [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the optimum operating parameters such as melting temperature, casting speed and roll gap. Yang et al [44] studied the processing stability of the twin-roll thin strip casting of the AZ31 alloy and the influence of process factors on the strip structure.…”
Section: Superplastic Forming Of Wrought Magnesium Alloysmentioning
confidence: 99%